A combination of histological analyses and uniaxial tensile tests to determine the material coefficients of the healthy and atherosclerotic human coronary arteries. Issue 2 (April 2015) - Karimi, Alireza; Navidbakhsh, Mahdi; Shojaei, Ahmad
Highlights: The key role of fiber orientation was explicitly added into a proposed material model. The CNOM was used to determine the material coefficients of human coronary samples. Regardless of loading direction, atherosclerotic arteries were stiffer than healthy ones. The optimized fiber angles were well compared to the experimental histological data. The stored energy function of the healthy arteries was higher than that of atherosclerosis. Abstract: Atherosclerosis is considered as the most severe form of cardiovascular diseases as it alters the structure of the elastin and collagen and, consequently, the mechanical properties of the artery wall. The role of collagen fibers orientations in the mechanical properties of the healthy and atherosclerotic human coronary arteries so far has not been well determined. In this study, a fiber family based constitutive equation was employed to address the mechanical behavior of healthy and atherosclerotic human coronary arteries using the combination of histostructural and uniaxial data. A group of six healthy and atherosclerotic human coronary arteries was excised at autopsy and histological analyses were performed on each artery to determine the mean angle of collagen fibers. The preconditioned arterial tissues were then subjected to a series of quasi-static axial and circumferential loadings. The key role of fiber orientation was explicitly added into a proposed strain energy density function. The constrained nonlinear optimization method was used to determine the material coefficients based on the axial and circumferential extension data of the arteries. The material coefficients of coronary arteries were given with R 2 ≥ 0.991. The results regardless of loading direction revealed a significant load-bearing capacity and stiffness of atherosclerotic arteries compared to the healthy ones ( p < 0.005). The optimized fiber angles were in good agreement with the experimental histological data as only 2.52% and 10.10% differences were observed for the healthy and atherosclerotic arteries, respectively. The stored energy function of the healthy arteries was found to be higher than that of atherosclerotic ones. These findings help us to understand the directional mechanical properties of coronary arteries which may have implications for different types of interventions and surgeries, including bypass, stenting, and balloon-angioplasty.